Taylor Rule Under Financial Instability - Cihak, Martin (IMF Working Papers; Working Paper, 2008)
This paper contributes to the analysis of monetary policy in the face of financial instability. In particular, we extend the standard new Keynesian dynamic stochastic general equilibrium (DSGE) model with sticky prices to include a financial system. Our simulations suggest that if financial instability affects output and inflation with a lag and if the central bank has privileged information about credit risk, monetary policy that responds instantly to increased credit risk can trade off more output and inflation instability today for a faster return to the trend than a policy that follows the simple Taylor rule with only the contemporaneous output gap and inflation.